LIVELIHOOD ATTRIBUTES OF POULTRY FARMERS IN ILORIN, KWARA STATE, NIGERIA - J. O. Ifabiyi; R. O. Sanusi; F. E. Evwierhurhoma; I. G. Ma'aji (مجلة الأنبار للعلوم الزراعية)
Poultry production is an essential source of livelihood as it provides subsistence and employment opportunities in Nigeria's poultry value chain activities. This study assessed the livelihood attributes of poultry farmers in Ilorin, Kwara State, Nigeria. Three-stage sampling was used to select 150 farmers for this research work. Descriptive statistics such as frequency, percentage, and mean were employed to analyze the data. The findings showed that the radio, internet/social media, and family were key sources of information on poultry production. Also, involvement in other income-generating activities (mean=4.14) was the highest-ranked financial asset. Owned/leased poultry pens/houses (mean=4.15) were the highest-ranked physical asset. Networking with other poultry farmers/agencies for resources (mean=4.37) was the highest-ranked social asset. Being physically fit to manage poultry production activities (mean=4.55) was the highest-ranked human asset. Access to water for poultry production (mean=4.31) was the highest-ranked natural asset. The livelihood status of the poultry farmers (3.93±0.93) was categorized as high. The study concluded that poultry production was a vital livelihood for the farmers. It therefore recommends supporting extension services for all poultry farmers to enhance their livelihoods and incomes. It is also essential for the government to provide livelihood incentives such as financial support and tax relief, as well as to subsidize poultry farming equipment to ensure that the farmers have the needed resources/assets and to boost their productivity